A revision of the genus Morophagoides Petersen (Lepidoptera, Tineidae) from Japan - Osada, Yohei; Sakai, Makoto; Hirowatari, Toshiya (Zootaxa, 2015)
Taxonomy of the Japanese species of the genus Morophagoides Petersen, 1957 is revised. Previously four species, namely Morophagoides ussuriensis (Caradja, 1920), M. moriutii Robinson, 1986, M. occidentalis Osada, Yoshimatsu, Sakai and Hirowatari, 2014 and M. meridianus Osada, Yoshimatsu, Sakai and Hirowatari, 2014 were recognized for the Japanese fauna. In the present study, four new species, M. breviculus sp. nov., M. robinsoni sp. nov., M. aquilonis sp. nov. and M. yakuensis sp. nov., from Japan are described based on adult characters. The potential synapomorphy of this widely distributed genus is proposed. In addition, the distribution pattern of the genus in Japan is discussed.